A Brief Overview of the Tax Compliance Literature Specific to Experimental Studies - Erhan Çelik; İsa Sağbaş (Maliye Çalışmaları Dergisi)
Tax compliance is the complete and timely fulfillment of taxpayers’ tax obligations as per tax laws and regulations. Notably, the survey method has mainly been used in the tax compliance studies conducted in Turkey.In the international literature, many studies can be encountered that used both survey and experimental methods. Despite the comprehensive literature on tax compliance in Turkey and the international literature, studies on tax compliance in Turkey involving laboratory experiments can be said to be rare. This study aims to provide information about experimental studies and contribute to the Turkish literature in order to increase both the quantity and quality of experimental studies carried out in Turkey on tax compliance. This study only performs a literature review of experimental studies in which students have taken part as subjects. The study results reveal increases in tax rates to reduce tax compliance, increases in audit rates to increase tax compliance, and increases in the level at which taxpayers trust the tax administration to increases tax compliance.